Rancang Bangun Sistem Informasi Point of Sale (POS) Berbasis Web dengan Manajemen Stok pada Toko Warsidi - Izzazi, Syahrul; Budihartono, Eko (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
Warsidi Store is a retail business that still performs sales transactions, inventory management, and report generation manually. This condition leads to inefficient data processing, increases the risk of recording errors, and delays report preparation and decision-making. This study aims to design and develop a web-based Point of Sale (POS) Information System integrated with inventory management to improve sales transaction processing, inventory control, and report generation more effectively and efficiently. The system was developed using the Waterfall software development methodology, which consists of requirements analysis, system design, implementation, testing, and maintenance. The application was built using PHP with the CodeIgniter 3 framework, MySQL as the database management system, and supporting technologies including HTML, CSS, JavaScript, Bootstrap, and jQuery. System testing was conducted using the Black Box Testing method to verify that all system functions operated according to user requirements. The results indicate that the developed system is capable of managing product data, sales transactions, inventory, customer data, operational expenses, and automatically generating sales and inventory reports. In addition, the system automatically updates stock quantities after each sales transaction, thereby improving inventory accuracy. Based on the testing results, all major system functionalities operated successfully and were declared valid according to the specified functional requirements. Therefore, the developed web-based Point of Sale (POS) Information System can improve the effectiveness, efficiency, and accuracy of operational management at Warsidi Store.